The Correlation Between Vocabulary Mastery and Students’ Descriptive Writing Skills - Lisa Lisa; Sri Normuliati (UIBU, 2023)
Vocabulary mastery and writing is an important part of learning. Regarding writing, there are various types of text in English subjects, one of which is descriptive text. That's why researchers want to know whether there is a correlation between vocabulary mastery (X) and students' descriptive writing skills (Y) class X.2 at SMAN 4 Palangka Raya. For this method used quantitative research, correlational design. Using random sampling so that the class chosen is X.2, number of students is 29. Data collection tools used multiple choice and essay tests. Data were analyzed using simple linear regression. Based on research results. The average student test score was 82.07 for vocabulary mastery and an average score of 67.69 for descriptive writing skills. The research results shown that there is no correlation between vocabulary mastery and students' descriptive writing skills, with a correlation significance of 0.744 which is greater than 0.05 (probability value) which means H0 is accepted while Ha is rejected. The correlation value (R) is 0.063 and the R square value is 0.004, which means the influence of variables X and Y is 0.4%. So, students must be improving skill for writing not only focused on vocabulary mastery.